Hydrolytic Cationic Ester Microparticles for Highly Efficient DNA Vaccine Delivery. Issue 20 (10th May 2013) - Zhang, Lei; Sinclair, Andrew; Cao, Zhiqiang; Ella‐Menye, Jean‐Rene; Xu, Xuewei; Carr, Louisa R.; Pun, Suzie H.; Jiang, Shaoyi
Abstract DNA vaccination holds great potential to be a safer and more efficient alternative to traditional vaccination strategies, but the current lack of nontoxic and effective delivery systems is the greatest impediment to its clinical implementation. In this work, a convenient one‐step method is used to prepare a degradable "microgel" delivery platform, featuring hydrolytic esters. Prior to hydrolysis, these micrometer‐sized gel particles can effectively condense DNA due to their positive surface charge. Upon entering antigen‐presenting cells (APCs), the microgels can be hydrolyzed to nontoxic zwitterionic polymers, consequently releasing the DNA and inducing phagosomal escape. Surface charge, DNA loading, cytotoxicity, and gene transfection efficiency of the hydrolysable microparticles with different tertiary to quaternary amine ratios are systematically studied. Nonhydrolysable counterparts and commercially developed PLGA‐CTAB particles are used as the control. The passive targeting effect is further evaluated by blocking the phagocytosis pathway of the cells. The hydrolytic microgels prepared in this study possess great potential to become a platform for DNA vaccine delivery.